Mapping the Contrast Sensitivity of the Visual Field With Bayesian Adaptive qVFM - Xu, Pengjing; Lesmes, Luis A.; Yu, Deyue; Lu, Zhong-Lin (Frontiers in Neuroscience, 2020)
Current clinical evaluation, which focuses on central vision, could improve characterization of residual vision with peripheral testing of visual acuity, contrast sensitivity, color vision, crowding, and reading speed. Assessing more than light sensitivity, a comprehensive visual field map (VFM) of functional vision would be valuable for detecting and managing eye diseases. In a previous study, we developed a Bayesian adaptive qVFM method that combines a global approach for preliminary assessment of the VFM’s shape, and a local approach for assessment at individual retinal locations. The method was validated in measuring the light sensitivity map. In this study, we extended the qVFM method to measure contrast sensitivity across the visual field. In both simulations and psychophysics, we sampled 64 visual field locations (48 x 48 deg) and compared the qVFM method with a procedure that tested each retinal location independently (qFC; Lesmes et al., 2015). On each trial, subjects were required to identify a single optotype (size: 2.5 x 2.5 deg), one of ten filtered Sloan letters. To compare the accuracy and precision of the two methods, three simulated eyes were tested in 1280 trials with each method. In addition, data were collected from ten eyes (5 OS, 5 OD) of five normal observers. For simulations, the average RMSE of contrast threshold estimates with the qVFM and qFC methods were 0.037 and 0.041 after 1280 trials (all in log10 units). The average SD of qVFM and qFC estimates were 0.032 and 0.041 after 1280 trials. The estimated within-run variability (68.2% HWCIs) were comparable to the estimated cross-run variability (SD). For psychophysics, the average HWCI of qVFM estimates across the visual field decreased from 0.33 on the first trial to 0.072 after 160, and to 0.060after 320 trials. The RMSE of qVFM and qFC estimates started at 0.26, decreased to 0.12 after 160 and to 0.11 after 320 qVFM trials. The qVFM provides an accurate, precise, and efficient mapping of contrast sensitivity across the entire visual field. The method could find potential clinical applications in monitoring vision loss, evaluating therapeutic interventions, and developing effective rehabilitation for visual diseases.